Kontribusi Pemerintah Dalam Mendukung Manajemen Pengelolaan Museum Pusaka Nias Sebagai Destinasi Wisata - Imel Febri Santi Harefa; Sudirman Lase; Herlina Saragih; Roida Lumbantobing (LPPM Politeknik Pratama, 2023)
The aim of this research is to determine the government's contribution in supporting the management of the Nias Heritage Museum and to understand the management of tourism management at the Nias Heritage Museum as a tourist destination. This research uses a qualitative method with a descriptive approach. The results obtained in the research are that the Nias Heritage Museum received contributions from the government and the management of the Nias Heritage Museum by implementing strategies in its development. The Nias Heritage Museum is the only museum on the Nias Islands which was founded by Pastor Johannes M. Hammerle OFMCap as a forum for preserving the nature, history and culture of Nias. The Nias Heritage Museum is not only a place to collect collections of Nias heritage objects, but also as a place for recreation. Contributions from the government include donations in the form of programs, funds, ideas, energy and actions provided. Meanwhile, management includes planning, organizing, directing and controlling.